Corporate social responsibility and internal control in Venezuelan state enterprises: a praxiological approach from institutional actors in Portuguesa (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2026)
This article explores, from a praxiological perspective, the relationship between Corporate Social Responsibility (CSR) and internal control mechanisms in three state-owned enterprises in Portuguesa State, Venezuela: BUSPORTUGUESA, S.A., CORSODEP, and ESOMEP. It analyzes the meanings, practices, and tensions constructed by institutional actors—presidents and managers—in their daily exercise within a context marked by institutional uncertainty, resource scarcity, and weak normative frameworks. Using a qualitative, hermeneutic, and field-based approach, semi-structured interviews were conducted with the highest-ranking officials of these organizations. Findings reveal a limited and moralistic understanding of CSR, reduced to notions of “personal responsibility” and “revolutionary ethics,” without strategic articulation with internal control systems. Moreover, reactive control practices centered on external audits, absence of formal risk management policies, disconnection from stakeholders, and a strong reliance on informal logics for decision-making were identified. These results highlight a structural gap between normative mandates and situated action logics, where actors negotiate, resist, or resignify CSR according to their interests and contextual conditions. Based on these findings, conceptual and operational guidelines are proposed to strengthen a culture of social responsibility and ethical control in Venezuela’s public sector, with regional relevance and potential for replication in similar contexts
Keywords: corporate social responsibility; internal control; organizational praxis